If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4p + -1p = -9 Combine like terms: 4p + -1p = 3p 3p = -9 Solving 3p = -9 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by '3'. p = -3 Simplifying p = -3
| 2x^2+2y^2-28x+12y+114=0 | | (12x8/4-4) | | 2x+3y=35-x | | 2x^2+-7x+10.34=0 | | M+6=3M-4 | | -125=-5(1+8x) | | 5(5v-7)=-135 | | -6(4v-8)-6=234 | | -384=-6(8-8n) | | 8(8+3x)=88 | | 102=8(1+6n)-2 | | 24+p=8 | | 3x-5(5x-3)=191 | | 4x-7x=4-25 | | 7m+4(m+6)=122 | | -8(6k+5)=248 | | -65.276=7.2(9c+1) | | -91=7v-7(6v-7) | | 49x=1/3 | | 4/6x=1/3 | | -249=-7(1+7v)+3 | | 26ab/13a | | 18x-41=3x-11 | | 6(4x-6)=132 | | 8*x-3/3x=2 | | -96=-6(6p+4) | | 4x-1=-16 | | (2x)+12=6-(4x) | | M-1/2_m-2/3=m-4/7 | | 0,5x=11 | | (2x)+12=(4x)-6 | | -12ab+8ab+7ab= |